C++ rush: interactive game in learning computer language for novice / Muhammad Salman Hakim Shaiful Nizam, Arifah Fasha Rosmani - Shaiful Nizam, Muhammad Salman Hakim; Rosmani, Arifah Fasha (College of Computing, Informatics and Media, UiTM Perlis, 2023)
C++ is one of the fundamental programming languages that are simple to learn and aid in understanding the fundamentals of all types of coding. With a full understanding of C++, migrating to other programming languages would be easy since the basic fundamentals have been grasped. The goal of this project is to learn C++ syntax, identify appropriate gamification elements, and incorporate multimedia principles into the design and development of the interactive C++ Rush game for computer language beginners. Another goal of this project is to evaluate the usability of the developed programming game through a questionnaire. For this project, the methodology used is agile because iterative development is one of its components. Agile methodology has six phases involved: requirements, design, development, testing, deployment, and review. For this research, usability testing has been conducted with 30 participants. Most of the users agree that gamification can transform a complex and difficult subject into something really enjoyable. In conclusion, this project has enabled the user to learn effectively about C++. Future works may include more programming language variety.